Pre‐cold acclimation promotes cryoprotectant accumulation and enhances freezing tolerance of Meloidogyne incognita. Issue 6 (13th April 2020) - Wang, Yuanzheng; Liu, Chen; Ren, Ping; Li, Yingmei
Abstract: Strong evidence suggests that cryoprotectant accumulation during pre‐cold acclimation protects cells against freezing injuries caused by cellular dehydration. In this study, the concentrations of trehalose and glycerol were measured in Meloidogyne incognita and it was found that both cryoprotectants were significantly accumulated in second‐stage juveniles (J2) of M. incognita after acclimation at 4°C. However, compared with non‐acclimated samples, only a higher level of trehalose was induced in the egg masses of M. incognita in response to cold treatment. Further characterizations indicated that pre‐cold acclimation efficiently accelerated the speed of larvae hatching from egg masses that were subjected to freezing at −1°C. In addition, the survival rate and pathogenicity of M. incognita J2 that had been acclimated prior to freezing were significantly enhanced when compared with non‐acclimated J2 individuals. As far as we know, this is the first time that this phenomenon has been reported in M. incognita .